Interaksi Dinamis Faktor Ekonomi terhadap Kesejahteraan Petani di Provinsi DI Yogyakarta: Pendekatan Granger Causality - Indrawan Firdauzi; Fitri Amalinda Harahap; Asmi Ayuning Hidayah; Muhammad Farid Alfarisy (Diponegoro Journal of Economics, 2025)
The agricultural sector is one of Indonesia's economic sectors. With a comparison of land area and overall production, the province of D.I. Yogyakarta ranks among the largest producers in Indonesia. The inadequate well-being of farmers continues to be a pressing concern in the Special Region of Yogyakarta. This study examines the effects of the interconnections among farmers' exchange rates, poverty, consumer price indices, inequality, and inflation on farmers' well-being in the Special Region of Yogyakarta. Utilizing secondary data sourced from the Central Statistics Agency (BPS) of Yogyakarta Province spanning from 2005 to 2023 in a time series format, we employed the Granger Causality model to examine the interrelationship among the farmers' exchange rate, inflation rate, poverty, and inequality in Yogyakarta Province. Our analysis revealed that the one-way link over the long term indicated that only the consumer price index had a beneficial impact on the farmer's exchange rate. Moreover, inequality adversely impacts the farmers' exchange rate, signifying that an increase in provincial inequality results in a decline in farmers' income. In examining causal relationships, several noteworthy discoveries emerged, including that inflation impacts inequality, which subsequently affects the farmers' exchange rate, and the farmers' exchange rate influences the consumer price index. As a novel contribution, this paper presents the first attempt to examine the factors influencing farmer welfare in the Province of DI Yogyakarta. We investigate the potential causal effects of key economic variables—including inequality, inflation, and exchange rates—on farmers.